Evaluation of Forensic Postmortem Examination Training on the Model in Context of Structured Scenario - Zeybek, Volkan; Acar, Kemalettin; Dereli, Ayşe Kurtuluş; Kara, Cüneyt Orhan (The Bulletin of Legal Medicine, 2018)
Introduction: Forensic postmortem examination is an issue that physicians have difficulties and have legal problems. It would be appropriate to add applications that are more memorable and appealing to the students for forensic postmortem examination education in medical faculties. This study was conducted in order to measure the results of the "forensic postmortem examination education on the model in the context of a structured scenario", which may be a good model for the application of interactive methods, at the Faculty of Medicine of Pamukkale University.Material and Methods: Eighty-eight 5th term students who were in forensic medicine training and 52 6th term students who were in public health training participated in the study. The knowledge and skill levels before and after the training and the opinions and recommendations about the education were evaluated and compared with standard forms.Results: When pre-test and post-test answers are evaluated; the positive difference between the pre-test and post-test answers of all the students was statistically significant in which the level of knowledge was assessed, except for the first question’s answer in 5th term students. When the forms of opinions and recommendations are examined; it was understood that the vast majority of the students had confidence in themselves in the practice of postmortem examination and the decision of the autopsy which they would encounter in the future, all students who gave written feedback reported that the education was fruitful and useful and that they were pleased with this education.Conclusion: Our practice has been a successful practice in acquiring the skills of forensic postmortem examination which is in the pre-graduate medical education core curriculum. This practice can also set an example for other medical schools in the teaching of forensic postmortem examination.
Keywords: forensic medicine; postmortem examination education; undergraduate medical education